Robust offset-free speed tracking controller of permanent magnet synchronous generator for wind power generation applications - Kim, Seok Kyoon; Lee, Kyo Beum (Electronics (Switzerland), 2018)
This article presents a robust speed tracking algorithm for a permanent magnet synchronous generator utilized for wind power generation systems, considering the machine parameter and load uncertainties. There are two major contributions: (a) a disturbance observer is designed to exponentially estimate disturbances from the model-plant mismatches and severe load torque variations, and (b) it is included in a nonlinear cascade-type proportional speed tracking controller to establish the performance recovery and offset-free properties without the use of tracking error integrators. A simulation result numerically verifies the effectiveness of the proposed technique, where the PowerSIM software emulates a wind power generation system.
Keywords: Offset-free; Performance recovery; Permanent magnet synchronous machine; Speed tracking algorithm; Wind power generation